Anti theft design of car seat (mechanical) - Nurul Husna, Mohamad Shariff (2009)
This report is an outcome of the work I have carried out in doing and completing my final year project, the Anti Theft Design of Car Seat. This report presents a new anti theft design of car seat prototype designed for the automatic car locking system, with attention on user’s safety and surrounding impact. The overall task is analyzed and proper suggestions are developed to organize the operation of new type car lock system which will use a car seat as a locking medium. The report starts off with an introduction on car anti theft system and car lock system. Then a further introduction describe on the important of the car lock and its advantages towards car safety. Based on the information, a design of new seat model is made. Several sketches have been made and only a few have been selected based on the suitability of the system. Besides, material needed in this project will be listed and the system used will be selected. Next all the sketches will be draw into CATIA software .Each part of the new model are tested using finite element method to make sure that the strength and stiffness of the seat unit are suitable for everyday usage. The seat are design to be fully automated seat, thus the control system of the seat movement are made. This project is successfully completed when final model has proved to be fulfilling nearly every factor that needed in anti theft system and car seat system.